ESTAFETALI YUGURISH TEXNIKASINI MUSTAHKAMLASH (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article covers the issues of improving relay running training, strengthening running techniques and increasing the physical and mental training of participants. The article analyzes the important technical elements in the process of transmitting and receiving a baton (palochka), the stages of running, team coordination and methods of correctly performing movements in the start and finish. The training also provides methodological recommendations for the development of relay running techniques.